Antenatal laparoscopic management of ovarian cyst: a case report - N. A., Niyaf; G. O., Ravikanth; Doppa, Geeta; H. U., Bhavya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The frequency of adnexal mass in pregnancy ranges from 2% to 10%, dermoid cyst is the most common ovarian germ cell tumor during pregnancy which could be asymptomatic or symptomatic, management through laparoscopy must be considered as it provides several advantages, including reduced postoperative pain, analgesic use, hospitalization time and better cosmetic result. Here we are reporting a case of an unbooked 35 years old primigravida at 16 weeks and 4 days gestation with history of retention of urine. Ultrasound showed a live foetus of 16 weeks gestation with bilateral mild maternal hydroureteronephrosis and complex cystic mass of 13×10 cm in right lumbar region suggestive of ovarian mass. Patient was clinically stable, hence exploratory laparoscopy was taken up the next day. Intraoperatively, dermoid cyst was found in the right ovary. Right ovarian cystectomy was performed. She had an uneventful postoperative period and discharged. She was monitored for the rest of the pregnancy and it was uneventful. She had spontaneous full term normal vaginal delivery of female baby weighing 2.8 kg. Although the patient was clinically stable, large ovarian cyst are predisposed for future complications, hence antenatal diagnosis and appropriate intervention is crucial for good outcome.